Raising Returns : The Distribution of Health Financing and Outcomes in Yemen - Elgazzar, Heba A. (World Bank, Washington, DC, 2013)
Given relatively few resources and lagging health outcomes in Yemen, the quest for equitable, cost-effective health care delivery continues as long-term, sustainable development remains a priority. This paper assesses overall value for money of the health system mainly as indicated by an analysis of public expenditure trends from 1997 until 2008 and by the degree to which health care benefits are conferred equitably to the population. Total health expenditure in 2007 accounted for 5.2 percent of Gross Domestic Product (GDP), or only PPP$ 41 per capita, with nearly 70 percent sourced by direct household payments (67 percent). Despite recent improvements in health status, Yemen continues to lag behind countries of similar or lower income and health expenditure levels. Levels of health outcomes in Vietnam, Indonesia and the Kyrgyz Republic are 2 to 6 times better than levels found in Yemen regarding the proportion of infants with low birth weight, the prevalence of malnutrition amongst children, the rate of births delivered by skilled attendants, and the rate of coverage of antenatal services. Although health facilities are relatively evenly distributed across the population, the operational status and quality of these facilities is highly variable. The availability of pharmaceuticals at health facilities ranges from 31 percent of facilities having medications on site in the governorate of Al-Maharah to 94 percent in Amran. To more effectively alleviate inequities and inefficiencies in health service delivery in Yemen, national policies are recommended to more strategically prioritize resource allocation and develop innovative service delivery models to more efficiently connect rural communities.